The Significance of Students' Perception and Participation on Reading Comprehension at IAIN Padangsidimpuan - Ardi Oktapian; Dina Maileni; Juliana Juliana (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This article aimed to find out the influence of students’ perception and participation of Tadris English Department students toward Reading Comprehension learning during the Covid-19 Era at IAIN Padangsidimpuan. The data were collected through students’ perception questionnaires, students' participation questionnaires, and reading comprehension tests. This research was correlational research design using a quantitative method. The subject of the research was the students’ 2nd year English department programs at IAIN Padangsidimpuan. The research sample was taken by using Total population sampling. 65 students have been used as samples in this research. Simple linear regression and multiple regression formula were used to analyze the data. The research findings showed that first, there was a significant influence on students’ perception and their Students’ Reading Comprehension with a score (0.000 0.05). Second, there was a significant influence on students’ participation and reading comprehension with scores (0.000 0.05). Third, there was a significant influence between perception and participation on students reading comprehension with a score (0.000 0.05) at IAIN Padangsidimpuan